Survival of stemless humeral head replacement in anatomic shoulder arthroplasty: a prospective study - Magosch, Petra; Lichtenberg, Sven; Habermeyer, Peter (Journal of shoulder and elbow surgery, 2021)
Background - The long-term results of shoulder arthroplasty using stemless humeral head components with a mean follow-up period > 10 years were not available until now. The aim of this study was to evaluate the long-term results of shoulder arthroplasty using a stemless humeral head component. - Methods - Since 2005, we have documented stemless humeral head replacement prospectively. Seventy-five patients with a mean age of 57 years at surgery (40 hemi-shoulder arthroplasties [HSAs] and 35 total shoulder arthroplasties [TSAs], 38 women and 37 men) were clinically and radiologically followed up after a mean period of 126 months (range, 105-157 months). Functional results were documented using the age- and sex-normalized Constant-Murley score (CMS) (ie, relative CMS). - Results - The relative CMS improved significantly (P < .0001) from 56% preoperatively to 90% postoperatively. Its subcategories of pain (8 points preoperatively vs. 12 points postoperatively, P < .0001), activities of daily living (10 points vs. 15 points, P < .0001), range of motion (20 points vs. 29 points, P < .0001), and strength (7 points vs. 11 points, P = .011) improved significantly as well. There was no significant difference in preoperative CMS vs. postoperative CMS, as well as its subcategories, between HSA (44.8 points vs. 67.1 points, P < .0001) and TSA (44.4 points vs. 68.9 points, P = .004). Clinically and radiologically, we observed no loosening of the stemless humeral head component. Stress shielding around the humeral component was not detected. Upward migration of the humeral head was observed in 17.5% of patients (21.6% with HSA and 11.5% with TSA, P = .303). No implant failure was observed on the humeral side. At follow-up, 18.3% of patients had rotator cuff deficiency (13.9% with HSA and 25% with TSA, P = .280). Overall, 9.3% of stemless shoulder arthroplasties were revised to reverse TSAs (5% of HSAs and 14.3% of TSAs, P = .097). TSA showed a trend for a higher revision rate than HSA. Secondary glenoid wear occurred in 64.3% of HSAs, and none of the HSAs were converted to TSAs. We observed an incomplete radiolucent line < 2 mm in 30.4% and glenoid loosening in 11.4% of cemented glenoid components. Kaplan-Meier analysis revealed a 10-year survivorship rate of 96.5% and an estimated 13-year survivorship rate of 90.1% for stemless humeral components. - Conclusion - Stemless humeral head replacement showed no loosening and a significant improvement in shoulder function after a mean period of 11 years. The long-term clinical and radiologic results as well as the survivorship of anatomic shoulder arthroplasty using a stemless humeral head implant are comparable to the long-term results of standard stemmed anatomic shoulder arthroplasty.